The Effect of Differences in Variety and POC on The Growth and Production of Sunflowers (Helianthus Annuus. L) - Fitriyani, Desy; Kany, Putri Irene; Budiman, Budiman (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This study used a completely randomized block design (CRBD) consisting of two factors. Factor I included the Kanigara variety (V1), the Helina variety (V2), and the BM1 variety (V3). Factor II consists of control POC concentration (P1), POC concentration of 9 ml/L (P2), POC concentration of 12 ml/L (P3), and POC concentration of 15 ml/L (P4). The parameters observed for plant growth were plant height (cm), number of leaves (sheets), stem diameter (cm), leaf area (cm2), and flowering age (DAP). The parameters observed for production were flower diameter (cm), harvest age (DAP), total seed weight per plant (g), weight of 100 seeds (g), wet husk weight (g), and dry husk weight (g). The Kanigara variety was the best in terms of plant height, leaf area, flower diameter, and seed weight per plant. The Helina variety was the best in terms of number of leaves, flowering age, and harvest age, while the BM1 variety was the best in terms of stem diameter, weight of 100 seeds, and wet and dry husk weight. POC at 0 ml/L had a significant effect on all growth and production parameters. A significant interaction between variety and POC was found in wet and dry seed weight, with the highest results observed in the BM1 variety at 0 ml/L POC.